Ants climb plants because they cannot swim: ant presence on flowers during the flood season reduces the frequency of floral visitors. (17th July 2020) - Souza, Camila S.; Baronio, Gudryan J.; Weirich, Carlos E.; Oliveira, Andressa F.; dos Santos Ferreira, Bruno H.; Arruda, Rafael; Aoki, Camila
Abstract : Seasonal changes in environments may not only affect habitat connectivity but may also affect its use by species and their interactions. Thus, during the flood season, ants are forced to develop survival strategies such as vertical plant migration. According to this, it has been hypothesized that the presence of ants may directly affect plant‐pollinator interactions. Thus, we asked the following questions: (i) Are floral visitors of Hyptis brevipes expelled due to ant presence on inflorescences during the flood period? (ii) Is the ant effect mediated by the abundance of ants foraging on inflorescences? And, (iii) Does flower abundance predict the abundance of floral visits and ants? We experimentally sampled 59 H. brevipes plants with and without ants during the flooded season, and observed no differences in flower abundance between ant treatments. The probability of detaining floral visitors on H. brevipes increased with ant abundance and exceeded 50% possible repellency, but the probability of visitor deterrence was not related to flower abundance. Furthermore, the abundance of flowers did not predict the number of ants on H. brevipes individuals or the frequency of floral visits. Consequently, ant repelling effects are pronounced when there are more ants foraging on plants. However, the ant repelling effect can be mitigated when plants flourish all year‐round and exhibit higher concentrations of flowers in the dry months. Additionally, the different sexual functions of plants may present specific responses due to the explosive pollination mechanism associated with ant effects. Abstract : Ants were not foraging plants during the unflooded season, but during flooded season we found Camponotus, Crematogaster, Linepithema and Pseudomirmex climbing plants. Ants seem not to select plants to climb according to flower abundance. Ant presence in higher ant abundance reduces floral visit probability. From 30 ants per plant, there is a 50% more chance of visitor detaining.